Assessment of Fungal and Mycotoxin Contamination of Maize Grains Collected from Senatorial Zones of Benue State - Vange , Onyeche; Umeh , Ebele; Gberikon , Grace; Ogbonna , Innocent (Journal of Agricultural Policy, 2021)
Purpose: Assessment of fungal and mycotoxin contamination of maize grains collected from Senatorial Zones of Benue State was carried out in this study. Methodology: Maize samples were collected in sterile polythene bags, labelled according to the sample locations and taken to the laboratory for analysis. Isolation and identification of the fungi was carried out using dilution method and standard mycological procedures. Samples were plated on Potato Dextrose Agar (PDA) supplemented with 60ug ml-1 chloramphenicol as a bacteriostat and incubated at room temperature for mycological identification and biomass. Quantifications of aflatoxin in the maize samples was carried out using Specific ELISA kit. Findings: Results showed that there was a high level of fungal contamination found in maize grains in Benue State. Many (40%) of Zone A maize grains had a high level (≥ 3.1 × 107 cfu/g) of fungal contamination, 40% of Zone B maize grains also had (≥ 3.1 × 107 cfu/g) of fungal contamination. While 26.7% of grains purchased from Zone C had (≥ 3.1 × 107 cfu/g) of fungal contamination. It was also observed that none (0%) of Zone A maize grains had aflatoxin level above 6.57ppb, while 10% of Zone B seeds produced aflatoxin levels above 6.57ppb and 25% of maize seeds from Zone C had aflatoxin levels above 6.57ppb. It was also observed that Zone B maize grains had the highest aflatoxin level of 9.50ppb, followed by Zone C with 9.20ppb, while Zone A had the lowest aflatoxin level of 5.10ppb. High aflatoxin levels above the 5.0ppb recommended by Standard Organization of Nigeria (SON) as tolerance limit for maize grains were observed in many of the locations studied. Unique Contributions to Theory, Policy and Practice: Therefore, maize grains should be dried properly and stored in less humid environment to avoid fungal growth and aflatoxin production, so as to prevent public health issues among consumers.